Pengaruh Disiplin Kerja, Motivasi Kerja Terhadap Kinerja Karyawan Dengan Lingkungan Kerja Sebagai Variabel Intervening BUMD PT. Sumekar Kabupaten Sumenep - Rafif Hibatullah; S. Anugrahini Irawati (Jurnal Kajian Ilmu Manajemen (JKIM), 2021)
This study discusses the work discipline, work motivation, employee performance, and work environment. Research uses a quantitative approach, using path analysis. With the number of respondents 54. The purpose of this study was to test the influence of work discipline and work motivation on employee performance through the work environment as an intervening variable. Based on the results of the analysis, shows that work discipline and work motivation affect directly or indirectly on employee performance and through the work environment. 1) Work disciplines had a positive and significant effect on employee performance by tcount is 2,611 ttable 2.00758 with a significant level is 0.012 0.05. 2) Work motivation has a positive and significant effect on employee performance by tcount  is 2,240 ttable 2.00758 with a significant level is 0.030 0.05. 3) The work environment had a positive and significant effect on employee performance by tcount  3,351 ttable 2.00758 with a significant level is 0.002 0.05. 4) Work disciplines had a positive and significant effect on the work environmentby tcount  2,084 ttable 2.00758 with a significant level is 0.042 0.05. 5) Work motivation has a positive and significant effect on the work environment tcount 3.364 ttable 2.00758 with a signifcation level is 0.001 0.05. 6) Work discipline has a positive and significant effect on employee performance through the work environment with an indirect influence coefficient of 0.112776 with a tcount of 2.720275 ttable 2.00758 with a significance of 0.05. 7) Work motivation has a positive and significant effect on employee performance through the work environment with an indirect influence coefficient of 0.002257 with a tcount of 58.961679 ttable 2.00758 with a significance of 0.05